Funktionale 3D-Oberflächenkenngrößen in der Umformtechnik - Pfestorf, Markus (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1997)
For the tribological characterization of the topography the common two dimensional surface parameters like Ra or Rz are not very suitable. Thus, the development of new three dimenional surface parameters is essential. The basic parameters, which can be derived from a mechanical-rheological model, are the material area ratio as well as the open and closed void area ratio. The most important parameters are the maximum of the closed void area ratio a clm as well as the closed void volume. Aiming a reliable determination of the surface paramters, a measurement guideline was developed. It is also shown that the influence of the size of the evaluation area as well as the form divergence can be observed. The results from several tribological tests show that there is a correlation between the surface parameters and the tribological properties of the topography. The capability of the surface parameters in industrial application is shown in two different examples. The first one is the use in temper mill rolling. The wear of the rolls in 61 km was shown by the three dimensional surface parameters of cold rolled steel strip. In a press shop, studies were made how to use the surface parameters for the quality control of the steel shee